Development of Rasch-Based Item Banks for the Assessment of Work Performance in Patients with Musculoskeletal Diseases. - Mueller, Evelyn; Bengel, Juergen; Wirtz, Markus (Journal of Occupational Rehabilitation, 2013)
Purpose This study aimed to develop a self-description assessment instrument to measure work performance in patients with musculoskeletal diseases. In terms of the International Classification of Functioning, Disability and Health (ICF), work performance is defined as the degree of meeting the work demands (activities) at the actual workplace (environment). To account for the fact that work performance depends on the work demands of the job, we strived to develop item banks that allow a flexible use of item subgroups depending on the specific work demands of the patients' jobs. Methods Item development included the collection of work tasks from literature and content validation through expert surveys and patient interviews. The resulting 122 items were answered by 621 patients with musculoskeletal diseases. Exploratory factor analysis to ascertain dimensionality and Rasch analysis (partial credit model) for each of the resulting dimensions were performed. Results Exploratory factor analysis resulted in four dimensions, and subsequent Rasch analysis led to the following item banks: 'impaired productivity' (15 items), 'impaired cognitive performance' (18), 'impaired coping with stress' (13) and 'impaired physical performance' (low physical workload 20 items, high physical workload 10 items). The item banks exhibited person separation indices (reliability) between 0.89 and 0.96. Conclusions The assessment of work performance adds the activities component to the more commonly employed participation component of the ICF-model. The four item banks can be adapted to specific jobs where necessary without losing comparability of person measures, as the item banks are based on Rasch analysis.